The Role of Syntactic Class, Frequency, and Word Order in Looking up English Multi-Word Expressions - Lew, Robert (Lexikos, 2012)
Multi-word lexical units, such as compounds and idioms, are often problematic for lexicographers. Dictionaries are traditionally organized around single orthographic words, and so the question arises of where to place such complex lexical units. The user-friendly answer would be to include them primarily under the word which users are most likely to look up. But how do we know which words are likely to be looked up? The present study addresses this question by examining the roles of part of speech, word frequency, and word position in guiding the decisions of Polish learners of English as to which component word of a multi-word expression to look up in the dictionary. The degree of word frequency is found to be the strongest predictor, with less frequent words having a significantly greater chance of being selected for consultation. Then there is an independent part of speech-related preference for nouns, with adjectives being second, followed by verbs in third place. Words belonging to the remaining syntactic categories (adverbs, prepositions, conjunctions, determiners, and pronouns) are hardly looked up at all. However, word placement within the multi-word expression does not seem to matter much. This study has implications for dictionary makers in considering how to list multi-word-expressions.